Garlic and Cardiovascular Disorders: A Current Review of Literature - Eddy Yuristo (HM Publisher, 2023)
Garlic, a member of the Allium family, widely used as culinary and medicinal herbs since ancient histories, displays aptly described anti-inflammatory and antioxidant properties. Garlic’s therapeutic benefit is showed to be result of its constituent organosulfur compounds. Previous study reported garlic to possess several benefits on cardiovascular health including antihypertensive, anti-atherosclerotic, and antilipidemic activities. This review elaborates the phytochemical composition, pharmacological activities, mechanism of actions, and current clinical evidence of garlic in mitigating cardiovascular disease.